Vancomycin Dosing in Obese Patients: Special Considerations and Novel Dosing Strategies. Issue 6 (June 2018) - Durand, Cheryl; Bylo, Mary; Howard, Brian; Belliveau, Paul
Objective: To review the literature regarding vancomycin pharmacokinetics in obese patients and strategies used to improve dosing in this population.Data Sources: PubMed, EMBASE (1974 to November 2017), and Google Scholar searches were conducted using the search terms vancomycin, obese, obesity, pharmacokinetics, strategy, and dosing . Additional articles were selected from reference lists of selected studies.Study Selection and Data Extraction: Included articles were those published in English with a primary focus on vancomycin pharmacokinetic parameters in obese patients and practical vancomycin dosing strategies, clinical experiences, or challenges of dosing vancomycin in this population.Data Synthesis: Volume of distribution and clearance are the pharmacokinetic parameters that most often affect vancomycin dosing in obese patients; both are increased in this population. Challenges with dosing in obese patients include inconsistent and inadequate dosing, observations that the obese population may not be homogeneous, and reports of an increased likelihood of supratherapeutic trough concentrations. Investigators have revised and developed dosing and monitoring protocols to address these challenges. These approaches improved target trough attainment to varying degrees.Conclusions: Some of the vancomycin dosing approaches provided promising results in obese patients, but there were notable differences in methods used to develop these approaches, and sample sizes were small. Although some approaches can be considered for validation in individual institutions, further research is warranted. This may include validating approaches in larger populations with narrower obesity severity ranges, investigating target attainment in indication-specific target ranges, and evaluating the impact of different dosing weights and methods of creatinine clearance calculation.